ELABORATION OF APPROACHES TO THE STANDARTIZ OFATION HELICHRYSUM ARENARIUM (1.) MOENCH IN PLANT MIXTURES - A. B. Goudzenko; A. A. Tsourkan (Фармация и фармакология (Пятигорск))
Marker for qualitative and quantitative standardization of Helichrysum arenarium (L.) Moench. flowers in the plant mixtures was determine. As a marker of Helichrysum arenarium Moench. flowers can be used flavonoid apigenin. HPLC method of determination flavonoid apigenin in raw materials and plant mixtures of flowers Helichrysum arenarium (L.) Moench was developed. Contents of apigenin in the raw plant flowers were in the range from 0,1453 ± 0,0068% to 0,1657 ± 0,0085%, in terms of the dried materials. It is shown, that the presence and content of apigenin flowers Helichrysum arenarium (L.) Moench can be standardized in the mixtures with the following plant:flowers, leaves and fruits of genus Crataegus L., roots of Althaea officinalis L., roots of Glycyrrhiza glabra L., roots of Cichorium intybus L., roots of Taraxacum officinale Web., cones of Humulus lupulus L., herb of Leonurus cardiaca L., herb of Hypericum perforatum L. and seeds of Linum usitatissimum L.